Evaluation of the contralateral ear in patients with unilateral chronic otitis media - Pardhi, Krupal A.; Pathak, Netra A.; Shinde, Kiran J. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Unilateral chronic otitis media (COM) is a condition likely to affect the other side also caused by various etiological factors. If diagnosed and intervened in time, the progression of the disease can be prevented and ear can be protected from various sequelae. Hence, it is important to assess and evaluate the contralateral ear (CLE) completely. Methods: A prospective study of 12 months was conducted in the Otorhinolaryngology department, enrolling 80 patients with unilateral chronic otitis media. The CLE defined as the asymptomatic ear without ear discharge or any other complaints. Otoscopy, pure tone audiometry, tympanometry and X-ray mastoid done on patients. The results were recorded and analysed. Results: On otoscopic findings 76.36% patients in mucosal and 88% patients in squamosal showed abnormalities in CLE. Pure tone audiometry (PTA) showed 75% patients had hearing loss in CLE 46.25% conductive hearing loss (HL), 11.25% sensorineural HL and 17.5% mixed HL in CLE. In squamosal type of COM 76% patients had hearing impairment as compared to mucosal type 74.54%. In tympanometry findings 58.75% patients had type B curve in CLE. Radiographic finding of CLE showed sclerotic mastoid air cells 32% in squamosal and 9.09% in mucosal type. Conclusions: Approximately 80% patients with unilateral COM have abnormal ear findings in CLE. Squamosal type of unilateral COM had more chances of abnormalities in CLE. In this study results showed that the CLE can also be affected in unilateral COM.